Two 1993 Kamchatka earthquakes - Johnson, Jean M.; Tanioka, Yuichiro; Satake, Kenji; Ruff, Larry J. (Pure and Applied Geophysics PAGEOPH, 1995)
Two earthquakes occurred in 1993 off southern Kamchatka. They have similar surface wave magnitudes, focal mechanisms, and depths, but have distinctly different characteristics. The November earthquake is a standard or “impulsive” M7 underthrusting event. The June earthquake is a tsunamigenic or “low-stress-drop” event with several unusual characteristics, including a large, diffuse aftershock zone, directivity, and a long source time function. The 1993 earthquakes ruptured a segment of the Kamchatka Arc which has not ruptured since 1904. The 1993 earthquakes seem to signal the midpoint in the southern Kamchatka seismic cycle. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/43211/1/24_2004_Article_BF00874387.pdf